Photosynthetic microbial fuel cell with polybenzimidazole membrane: synergy between bacteria and algae for wastewater removal and biorefinery. Issue 3 (March 2018) - Angioni, S.; Millia, L.; Mustarelli, P.; Doria, E.; Temporiti, M.E.; Mannucci, B.; Corana, F.; Quartarone, E.
Abstract: Here, we demonstrate a very efficient simultaneous approach of bioenergy generation from wastewater and added-value compounds production by using a photosynthetic microalgae microbial fuel cells (PMFC), based on polybenzimidazole (PBI) composite membrane as separator. The use of PBI was proved to be very promising, even more convenient than Nafion™ in terms of energy performances as well as cost and sustainability. This polymer is also easily autoclavable, so allowing a re-use of the separator with a consequent beneficial cost effect. Two PMFCs were investigated: 1) Pt electrocatalysed and 2) Pt-free. They were operated as microbial carbon capture (MCC) device under continuous illumination, by using a domestic wastewater as anolyte and Scenedesmus acutus strain in the catholyte. The Pt-based cell allowed to generate higher volumetric power density (∼400 mW m −3 ) after more than 100 operating days. This resulted in an improved wastewater treatment efficiency, determined in terms of normalised energy recovery ( NER > 0.19 kWh kgCOD −1 in case of Pt). The CO2 fixation of the PMFC-grown microalgae leaded to a high accumulation of added-value products, namely pigments and fatty acids. A significant quantity of lutein was observed as well as a relevant amount of other valuable carotenoids, as violaxanthin, astaxanthin and cantaxanthin. The lipids were even excellently accumulated (49%dw ). Their profile was mainly composed by fatty acids in the range C16-18, which are particularly indicated for the biofuel production. These results demonstrate the feasibility and the implemented sustainability of such PMFCs as a great potential technology for the wastewater treatment and the simultaneous production of valuable products.